2011
DOI: 10.4028/www.scientific.net/amr.287-290.805
|View full text |Cite
|
Sign up to set email alerts
|

Comparision of Direct Quenching and Reheat Quenching Process on Microstructure and Mechanical Properties of a High Strength Steel

Abstract: The effects of direct quenching and tempering (DQ-T) process and conventional reheat quenching and tempering (RQ-T) processes on the microstructure and mechanical properties of a high strength low alloy steel were investigated. In the as-quenched DQ steel, prior austenite grains are elongated parallel to the rolling direction, whereas the as-quenched RQ steel mainly consists of equiaxed grains; The DQ process was found to enhance the hardenability of steel effectively. The tensile strength and yield strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It has been shown that quenching process can effectively improve the strength of the steel (Hui et al, 2002). The hardness and strength gradually increase with the increases of quenching temperature, but when the quenching temperature exceeds 1000°C, the changes in hardness and strength are not significant (Duan et al, 2012). The mechanical properties of steel after fire exposure are closely influenced by the microstructure of the material (Azhari et al, 2017; Azhari et al, 2018).…”
Section: Residual Mechanical Properties After Fire Exposurementioning
confidence: 99%
“…It has been shown that quenching process can effectively improve the strength of the steel (Hui et al, 2002). The hardness and strength gradually increase with the increases of quenching temperature, but when the quenching temperature exceeds 1000°C, the changes in hardness and strength are not significant (Duan et al, 2012). The mechanical properties of steel after fire exposure are closely influenced by the microstructure of the material (Azhari et al, 2017; Azhari et al, 2018).…”
Section: Residual Mechanical Properties After Fire Exposurementioning
confidence: 99%